دراسة تأثير الأنشطة البشرية والزراعية على بعض مؤشرات جودة مياه الشرب حالة دراسة: منطقة قسمين - عليا, تميم; نيصافي, إبراهيم; ناصر, رماز (Latakia University Journal -Biological Sciences Series, 2019)
نظراً لأهمية المحافظة على مصادر مياه الشرب وحمايتها من الملوثات المختلفة، ونتيجة وجود مؤشرات لتلوث مصادر مياه الشرب في منطقة قسمين دفعت السكان إلى تجنب استخدام مصادر مياه الشرب التقليدية في المنطقة. يتضمن البحث دراسة الخصائص الفيزيائية والكيميائية للمياه في ستة مصادر لمياه الشرب في منطقة قسمين. شملت الدراسة قياس كل من درجة الحرارة، والعكارة، والناقلية الكهربائية وpH وCOD و5BOD وتراكيز بعض العناصر الثقيلة مثل الحديد والنحاس والكادميوم والرصاص. أخذ عينات المياه من المصادر المذكورة شهريا على مدار عام كامل. أظهرت النتائج أن درجة الحرارة والناقلية وpH وتراكيز العناصر الثقيلة كانت ضمن الحدود المسموح بها حسب المواصفة السورية لمياه الشرب، بالمقابل تجاوزت قيم العكارة وCOD و5BOD الحد المسموح به حسب المواصفات القياسية السورية مما قد يشير إلى وجود بعض المؤثرات التي تسبب تلوث هذه المصادر المائية. Due to the importance of protecting drinking water sources from various pollutants, and the presence of indicators of contaminating drinking water sources in Qasmin area, people there avoid using the traditional sources of drinking water. The research includes studying the physical and chemical properties of water in the six sources of drinking water in Qasmin area which included measurement of temperature, turbidity, electrical conductivity , ph , COD , BOD5 and concentrations of some heavy minerals such as iron, copper, cadmium and lead. Samples of drinking water there were taken monthly for a year. The results showed that temperature, conductivity, ph and concentrations of heavy metals were within the allowed limits according to Syrian standards for drinking water. At the same time, values of turbidity, COD and BOD5 exceeded the allowed limits according to Syrian standards for drinking water, which indicate the presence of pollution sources that may cause contamination of these water sources.